Isolated scapular tuberculosis: an uncommon presentation of skeletal tuberculosis - Dev, Ghanshyam; Sharma, Shwait; Ilyas, Mohd (The European Research Journal, 2018)
Objective: The main objective of the study was to evaluate the radiological manifestations of isolated scapular tuberculosis. Methods: A prospective study was performed wherein 50 patients with the complaint of swelling in the scapular region were evaluated using various imaging modalities for scapular tuberculosis. Patients having features of scapular tuberculosis were subjected to fine needle aspiration cytology (FNAC) and histopathology for confirmation of diagnosis. Results: Four patients were diagnosed as having isolated scapular tuberculosis. All the four patients presented with lytic lesions in scapula with associated collections in adjacent muscles. All were subjected to anti-tuberculosis therapy (ATT). In two patients drainage of abscess was done. All patients showed excellent response to treatment at 6 months follow-up. Conclusion: Radiological investigations play a key role in early diagnosis of isolated scapular tuberculosis with excellent outcome with ATT and drainage of collection.